Factors associated with online dating among college students engaging in casual sexual behavior in China: cross-sectional study - Weiyong Chen; Zhongrong Yang; Qiaoqin Ma; Xin Zhou (Frontiers Media S.A., 2024)
ObjectiveThis study aimed to investigate the factors associated with online dating among college students engaging in casual sexual behavior, by understanding these factors, targeted intervention measures can be formulated for relevant departments to help college students better manage their sexual health and offer useful reference for the development of sexual health education.MethodsA cross-sectional survey was conducted using a stratified cluster sampling method. Demographic and behavioral information was gathered through questionnaires for univariable and multivariable logistic regression analysis.ResultsA total of 595 college students engaging in casual sexual behavior were included in the study, of whom 345 (57.98%) had found casual sexual partners through the internet. Multiple regression analysis indicated that male participants, those aged 20-21 years, those who had recently attended AIDS-themed lectures or health education classes at school, participants who were willing to engage in commercial sexual activities during online dating, participants who accepted sexual activities among men who have sex with men (MSM), those who reported having sexual intercourse with regular partners in the past year, participants who wanted to know if their online dating partners were HIV-diagnosed, those who had engaged in commercial sexual behavior in the past year and those who perceived themselves to be at risk of HIV infection were more likely to engage in online dating. Participants with general/disharmonious family relationships, those who consistently used condoms during casual sexual behavior and those who occasionally used condoms were less likely to engage in online dating.ConclusionThere were a certain extent proportion of casual partners among college students were sourced from the internet, indicating the profound influence of online dating on casual sexual behavior. Therefore, future research and intervention measures should focus on sexual health education and promotion on online dating platforms, strengthen regulations and guidance on college students' online dating behavior, and raise awareness of HIV prevention in this group.